The aetiology of preterm birth and risks of cerebral palsy and cognitive impairment : A systematic review and meta-analysis - Ylijoki, Milla; Sentenac, Mariane; Pape, Bernd; Zeitlin, Jennifer; Lehtonen, Liisa (John Wiley & Sons, 2024)
Aim The associations between the aetiology of preterm birth and later neurodevelopmental outcomes are unclear. A systematic review and meta-analysis examined the existing evidence. Methods The PubMed and Embase databases were searched for papers published in English from inception to 16 December 2020. We included original papers on the causes of preterm birth and the risks of cerebral palsy (CP) and suboptimal cognitive development. Two reviewers independently evaluated the studies and extracted the data. Results The literature search yielded 5472 papers and 13 were selected. The aetiology of preterm birth was classified under spontaneous or medically indicated delivery. A meta-analysis was performed, comprising 104 902 preterm infants from 11 papers on CP. Preterm infants born after a medically indicated delivery had a lower CP risk than infants born after spontaneous delivery, with a pooled odds ratio of 0.59 (95% confidence interval 0.40–0.86). This result was robust in the subgroup and sensitivity analyses. Cognitive development was reported in three papers, which suggested that worse outcomes were associated with medically indicated deliveries. Conclusion The aetiology of preterm delivery may contribute to the risk of CP and cognitive delay. Further research is needed, using individual-level meta-analyses to adjust for possible confounders, notably gestational age.
Keywords: cerebral palsy; placental insufficiency; PPROM; preterm infant; cognitive development; fi=Matematiikka|en=Mathematics|